Sex Determination From Recognizable Vertebrae - Ünlütürk, Özge; İşcan, Mehmet Yaşar (The Bulletin of Legal Medicine, 2014)
Sex determination is one of the first steps in human identification. Many parts of the skeleton have already being analyzed and appropriate techniques developed. Vertebrae are among the least studied bones yet its presence at a death scene is the most common of all. The purpose of this presentation is to analyze sexual variation in South African white and black populations from the Pretoria Bone Collection. The sample is composed of complete vertebrae from 144 individuals. Seven measurements were taken from each of the C7, T1, T11, T12 and L5 with a digital caliper sensitive to 0.01 mm. These bones were selected because of their being recognized easily due to their anatomy and position in the vertebral column. Sex differences were assessed using the discriminant function procedure in SPSS.  The analysis provided an accuracy rate of 89% in whites and 85% in blacks. When each bone with its seven dimensions entered into the stepwise procedure only 2 or less were selected to separate one sex from the other. Accuracy rate ranged from 89% in white and 84% in black T1s. The least dimorphic of all was 80% in white and 64% in black L5s. It is clear that vertebra is as dimorphic as many of the long bones. It has certain advantages over others because there are many of them in a crime scene. In studying vertebral column the difficulty is to identify the sequence of each bone when several are missing. This study used those that are readily identifiable.Keywords: Sex determination, Pretoria Bone Collection, vertebrae forensic anthropology, crime scene.
Keywords: sex determination; pretoria bone collection; vertebrae forensic anthropology; crime scene